The Manufacture of Two Yellow Azo Dyes - Alcasabas, Manolo Z. (College of Engineering, 1966)
The manufacture of the two yellow azo dyes, namely the Du Pont Brilliant Yellow and the Pontamine Yellow CH, begins with the nitration and terminates in the packing of the latter product. The former is used in part as a reagent for the production of the latter in the ethylation autoclave and in part as a finished product. The plant site proposed will be located in Valenzuela, Bulacan to minimize transportation costs in delivering the finished products to the various consuming industries. From the calculations, no break even point would be reached and so graph of it and accompanying shutdown point is omitted from the report.